Tata Kelola Administrasi Pemberdayaan dan Kesejahteraan Keluarga (PKK) di Kelurahan Mandan Kecamatan Sukoharjo Kabupaten Sukoharjo - Sri Riris Sugiyarti; Suwardi Suwardi; Achmad Choerudin (Jurnal Pengabdian Multidisiplin, 2024)
This community service activity is in collaboration with the Family Empowerment and Welfare (PKK) organization, Mandan Village, Sukoharjo District, Sukoharjo Regency. The problems faced in this organization are related to the management of administrative activities which are not well managed. This condition will make it difficult to administer important documents that can support the smooth running of PKK activities. This is because most of the PKK's activities are carried out without an administrative governance system. Likewise for other activities that are carried out without physical evidence but only in the form of verbal agreements without going through the stages of planning, implementation, reporting or evaluation. Based on these problems, the community service team at Slamet Riyadi University (Unisri) Surakarta provided outreach regarding the PKK administrative governance system in Mandan Village, Sukoharjo District, Sukoharjo Regency. The method of implementing activities is carried out by holding socialization which aims to provide a good overview of the document administration system for PKK activities. Furthermore, providing assistance regarding the administration of PKK activity documents. Based on the results of the evaluation of community service activities, the results showed that PKK members were able to make an agreement by going through the stages of planning, implementation, reporting and evaluation for PKK activities in a simple form.